Cachexia and tumour necrosis factor-alpha in cytomegalovirus infection. Issue 6 (June 1991) - Tilg, H; Vogel, W; Herold, M; Aulitzky, W E; Huber, C
Abstract : Although cachexia is a common feature of cytomegalovirus infection, little is known about its cause. To explore any contributory role that tumour necrosis factor-alpha (TNF) might have the serum concentrations of TNF in eight patients who developed CMV disease after liver transplantation were investigated. All patients exhibited pronounced and long lasting increases in TNF serum concentrations. Increased endogenous TNF concentrations were associated with weight loss and anorexia. In contrast, liver transplant recipients without CMV disease showed no weight loss.